PENGARUH KECERDASAN EMOSIONAL DAN KEADILAN PROSEDURAL KARYAWAN PADA KEPUASAN NASABAH - Widiari, Ida Ayu Rat (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The purpose of this study is to analyze the influence of emotional intelligence and procedural justice of employees on customer satisfaction in Branch Office of PT. Bank Pembangunan Daerah Bali, Renon, Denpasar. The number of samples taken were 140 customers with non-probability sampling method and accidental sampling, data were collected using questionnaire and analyzed by multiple linear regression techniques. The results show that emotional intelligence and procedural justice was influence on customer satisfaction positively. The implication of this research is that employees have to show better attitude in controllingtheir emotion and focus more to the interests of customers by providing fair treatment in accordance with procedures prevailed in endeavour to improve customer satisfaction
Keywords: emotional intelligence, procedural justice, customer satisfaction